Advancing diagnosis and treatment for human African trypanosomiasis in Nigeria: challenges and future directions - Zongo, Kelly; Emmanuel, Rolayo Toyin (Frontiers in Tropical Diseases, 2025)
Human African trypanosomiasis (HAT), commonly known as sleeping sickness, remains a significant health threat in sub-Saharan Africa. In Nigeria, the challenges of diagnosing and treating HAT are profound, especially in resource-constrained, remote areas. This article offers a perspective on the barriers to timely diagnosis and treatment of HAT in Nigeria, drawing from recent developments in diagnostic techniques and case management approaches. The focus is on improving the current diagnostic framework, decentralizing the validation process, and streamlining drug distribution to effectively halt the transmission of HAT. We discuss the potential of simple and rapid molecular diagnostics, particularly the lyophilized LAMP test, as a game-changer in resource-limited settings and the need for a national repository of drugs to ensure timely therapeutic interventions. This article also explores future directions for the elimination of HAT in Nigeria, highlighting the importance of policy reforms and increased investment in diagnostic infrastructure.